Evaluation of the Social and Psychological Changes Occurring in Elderly Living in Konya Province in Terms of Landscape Architecture During the Pandemic Process - Sertaç Güngör; Fatma Bütüner (Turkish Journal of Agriculture: Food Science and Technology, 2021)
Covid-19, which affects the whole world and is accepted as a pandemic by the world health organization, caused millions of people to die. The elderly are in the group with the highest risk of losing their lives due to the Covid-19 virus. Stricter restrictive / protective measures have been taken for the elderly in Turkey, as in the whole world. With this research, it is aimed to evaluate the sociological and psychological effects of the "elderly", who are one of the health risk groups of the society, in terms of landscape architecture, during the pandemic days when they had to experience various problems after the outbreak. In the study, face-to-face and online questionnaires were applied to individuals aged 50 and over on a voluntary basis. As a result of the study, it was determined that the implementation of curfews and restrictions for the elderly and the formation of an isolated lifestyle from other age groups caused an increase in loneliness and anxiety levels and negative psychological effects. It has been revealed that the activities that individuals will carry out in the green area, their conversations and socializing with their peers, and walks in the open area have a positive psychological and sociological effect for the elderly. It has been determined that the elderly who become lonely and depressed at home with the restrictions imposed under pandemic conditions want to be in green areas. The sociological and psychological positive effects of being in green areas and spending time, and the changes in the behaviour and emotions of the elderly who have pandemic restrictions paralleled the response of the participants to the questionnaire.